Prevalence of sexual problems and related help-seeking behaviors among mature adults in Brazil: data from the Global Study of Sexual Attitudes and Behaviors - Moreira Junior, Edson Duarte; Glasser, Dale; Santos, Djanilson Barbosa dos; Gingell, Clive (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Relatively little is known about the usual frequency of sexual activ- ity and how older individuals cope with sexual problems. The objective was to study sexual activity, prevalence of sexual problems and related help-seeking behaviors among middle-aged and older men and women in Brazil. DESIGN AND SETTING: Population survey, by Fundação Oswaldo Cruz. METHODS: Interviews were held with 1,199 Brazilians aged 40-80 years (471 men and 728 women). The standardized questionnaire investigated demographics, general health, sexual behavior, attitudes and beliefs. RESULTS: Overall, 92.6% of men and 58.3% of women had had sexual intercourse during the preceding year. More than half of the men and women had done so more than once a week. Early ejaculation (30.3%) was the commonest male sexual problem, followed by inability to reach orgasm (14.0%), erectile difficulties (13.1%) and lack of sexual interest (11.2%). For women, the commonest sexual problems were lubrication difficulties (23.4%) and lack of sexual interest (22.7%). Depression was a significant correlate of sexual problems, for men and women. More women than men had sought help for sexual problem(s) from a healthcare professional. CONCLUSIONS: The findings highlight the importance of encouraging greater use of avail- able healthcare services, including consultation with a medical doctor regarding sexual health. This should not only enable men and women to maintain satisfactory sexual function well into their later years, but may also result in overall improvement in the quality of healthcare.